Room Temperature Synthesis of Phosphine‐Capped Lead Bromide Perovskite Nanocrystals without Coordinating Solvents. (19th November 2019) - Ambroz, Filip; Xu, Weidong; Gadipelli, Srinivas; Brett, Dan J. L.; Lin, Chieh‐Ting; Contini, Claudia; McLachlan, Martyn A.; Durrant, James R.; Parkin, Ivan P.; Macdonald, Thomas J.
Abstract: The room temperature synthesis of perovskite nanocrystals (NCs) is typically achieved by employing a ligand‐assisted reprecipitation (LARP) method, which can be handled in air, and its products are comparable to what is obtained using the traditional hot‐injection method. However, the LARP method typically requires the use of coordinating polar solvents such as dimethylformamide, which are not appropriate for large‐scale production due to toxicity concerns and can also degrade or form defective perovskite NCs. Herein, an amine and oleic‐acid‐free room temperature synthesis of lead bromide perovskite NCs is reported that uses a combination of trioctylphosphine oxide and diisooctylphosphinic acid ligands. This combination of ligands provides a stable platform for the polar‐solvent‐free synthesis in air of fully inorganic CsPbBr3 (fwhm ≈ 14 nm, emission = 519 nm) and hybrid organic‐inorganic FAPbBr3 (fwhm ≈ 19 nm) NCs with photoluminescence emission between 530 and 535 nm, which is in line with the Rec. 2020 color standards. In addition, it is shown that compared to a traditionally used ligand combination, phosphine ligands can be easily removed from the surface of the NCs, which is important for the future development of this technology in optoelectronic devices. Abstract : Perovskite nanocrystals have been synthesized at room temperature without coordinating solvents, and this versatile approach can be used for both inorganic and hybrid organic‐inorganic perovskites. The methods presented are industrially scalable and provide new fundamental understandings into the surface chemistry of lead halide perovskite nanocrystals.